The Role Of Organizational Intelligence In Achieving Strategic Agility By Using The Complexity Leadership Theory - M. Mahmood, Zainab; A. Faris, Ali; G. Wadi, Ameer (Opción, 2019)
This study aims to identify the role of organizational intelligence in achieving strategic agility by using the Complexity leadership theory. Therefore, this study started with a problem expressed in a number of intellectual and ap- plied questions. The answer to it aimed to clarify the theoretical philosophy, intellectual connotations, and the applied capabilities for their variables cov- ered by the study, namely (Complexity leadership, organizational intelligence, and agility of organizations), and then diagnose the level of its importance, im- pact, and the possibility of applying it in universities. This study was applied to a group of associates who hold senior management positions in it, the study used a group of statistical analyses and tests using the statistical programs (SPSS 18 and EXCEL) and Barron’s equation. A special measuring tool was designed to collect the necessary data that serve the topics of the study. The study reached a set of conclusions, including: There is a direct, positive and strong impact for organizational intelligence on the agility of organizations in the sense of the contribution of administrative and adaptive leaderships and possible leadership in quickly responding to changes in the environment through agile strategies so that they apply the knowledge they possess in all their activities.